2020
DOI: 10.5802/smai-jcm.61
|View full text |Cite
|
Sign up to set email alerts
|

On the Scalability of the Schwarz Method

Abstract: Introduction and main resultsAn algorithm is said to be weakly scalable if it can solve progressively larger problems with an increasing number of processors in a fixed amount of time. According to classical Schwarz theory, the parallel Schwarz method (PSM) is not scalable (see, e.g., [2,7]). Recent results in computational chemistry, however, have shed more light on the scalability of the PSM: surprisingly, in contrast with classical Schwarz theory, the authors in [1] provide numerical evidence that in some c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Weak scalability results for the Laplace problem have been proven for more general chain-type geometries using various techniques, such as the maximum principle in [8] and a fully variational analysis in [9]. The most recent work on the topic without restrictive assumptions can be found in [10], where a propagation-tracking analysis based on graph theory and the maximum principle permitted a scalability analysis for very general decompositions. To our knowledge, there is no such analysis for Schwarz methods for time-harmonic wave propagation problems, where previous techniques no longer extend to, as the nature of the underlying equations is very different.…”
mentioning
confidence: 99%
“…Weak scalability results for the Laplace problem have been proven for more general chain-type geometries using various techniques, such as the maximum principle in [8] and a fully variational analysis in [9]. The most recent work on the topic without restrictive assumptions can be found in [10], where a propagation-tracking analysis based on graph theory and the maximum principle permitted a scalability analysis for very general decompositions. To our knowledge, there is no such analysis for Schwarz methods for time-harmonic wave propagation problems, where previous techniques no longer extend to, as the nature of the underlying equations is very different.…”
mentioning
confidence: 99%
“…= e 2λδ +e λL e 2λδ+λL +1 . Theorem 2 gives the same bound (8) for the convergence factors of PSM and OSM. This fact is not surprising.…”
Section: Convergence and Scalabilitymentioning
confidence: 68%
“…which is known to be not scalable; see, e.g., [3,8]. The scalability of PSM and OSM for different external conditions applied at the top and at the bottom of the domain is summarized in Table The behavior of the bounds ρ RR (δ, q), ρ DR (δ, q) and ρ NR (δ, q) with respect to q is depicted in Fig.…”
Section: Proofmentioning
confidence: 99%
“…It turns out that for a convergence analysis in the latter case it is not obvious how results and tools available in classical analyses can be applied. Therefore, in recent papers [2,3,4,5,6] this topic has been addressed and new results on the convergence of the Schwarz domain decomposition iterative method on a family of domains Ω M , M = 2, 3, . .…”
Section: Introductionmentioning
confidence: 99%
“…no balls are allowed that are contained inside Ω M . A first step towards a more general analysis can be found in [6], which analyzes how the error propagates and contracts in the maximum norm in a general geometry. It is shown that for a molecule with N -layers, it takes N + 1 iterations until the first contraction in the maximum norm is obtained.…”
Section: Introductionmentioning
confidence: 99%